2012
DOI: 10.1118/1.4769122
|View full text |Cite
|
Sign up to set email alerts
|

Rapid additive manufacturing of MR compatible multipinhole collimators with selective laser melting of tungsten powder

Abstract: Additive manufacturing is a very promising technique for the production of complex multipinhole collimators and may also be used for producing other complex collimators. The cost of this technique is only related to the amount of powder needed and the time it takes to have the collimator built. The timeframe from design to collimator production is significantly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 22 publications
(23 reference statements)
0
54
0
Order By: Relevance
“…By repeating this process a number of times a solid 3D object of intended shape could be fabricated [4]. Previous works in recent years have demonstrated the feasibility of using this method to build 3D part from a range of metal powders, including pure iron [5], stainless steel [6][7][8], hard tool steel [9,10], titanium alloys [11][12][13][14][15], nickel-base superalloys [4,[16][17][18], cobalt-chromium alloys [19][20][21], copper compounds [22][23][24], aluminum alloys [15,[25][26][27], refractory metals [28][29][30][31], metal matrix composites (MMCs) [2,[32][33][34][35], and even dissimilar metals (functionally gradient materials) [36,37]. Glass [38,39] and metal glass [40][41][42], quasicrystals [43] are also reported as potential SLM materials in this year.…”
Section: Introductionmentioning
confidence: 99%
“…By repeating this process a number of times a solid 3D object of intended shape could be fabricated [4]. Previous works in recent years have demonstrated the feasibility of using this method to build 3D part from a range of metal powders, including pure iron [5], stainless steel [6][7][8], hard tool steel [9,10], titanium alloys [11][12][13][14][15], nickel-base superalloys [4,[16][17][18], cobalt-chromium alloys [19][20][21], copper compounds [22][23][24], aluminum alloys [15,[25][26][27], refractory metals [28][29][30][31], metal matrix composites (MMCs) [2,[32][33][34][35], and even dissimilar metals (functionally gradient materials) [36,37]. Glass [38,39] and metal glass [40][41][42], quasicrystals [43] are also reported as potential SLM materials in this year.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al also obtained tungsten bulk with 82.9% of the TD by SLM from polyhedral powders and concluded that the balling tendency of tungsten is especially high because molten tungsten droplets tend to solidify before they can completely spread out over the surface of the sample [18]. In addition to these studies, a complex tungsten collimator (89.2% TD) was built by Deprez et al [19]; however, they did not discuss the processing in detail. From the above studies, it can be concluded that improved wetting conditions are required for the SLM of tungsten.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges in achieving compatibility with MRI are similar to those encountered in PET/MRI, with the added possibility of introducing eddy currents in the collimator. The availability of additive manufacturing technology [56] can aid in the manufacture of complex collimators that achieve effective radiation shielding while introducing divided components that minimise the possibility of eddy currents [57].…”
Section: Spectmentioning
confidence: 99%